Factors Associated with Expenditure on Animal Protein among Indonesian Households - Anna Vipta Resti Mauludyani; Ahmad Syafiq (Amerta Nutrition, 2023)
Background: Eating animal protein (AP) can prevent stunting in children under five, which currently is still 21.5%. Due to scarce resources, households had trouble distributing the cost and frequently had to choose between it and other food expenses.